FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN ANAK YANG MENGALAMI HOSPITALISASI - Marwan Riki Ginanjar; Septi Ardianty; Kartika Apriliyani (IKesT Muhammadiyah Palembang, 2021)
Introduction: Children with anxiety due to hospitalization will experience anxiety, worry about threats that are unclear, not secific and associated with feelings of uncertainty and helplessness. The factors related to anxiety were gender, hospital experience and nurse caring behavior. Objective of the research was to find out the correlation among sex, experience of being treated in a hospital, caring behavior of nurses with the level of anxiety in children who were hospitalized at Muhammadiyah Palembang Hospital in 2019. Method: This study used cross-sectional descriptive analytic. The number of sample was 32 preschoolers with the sampling technique wa purposive sampling. The analysis used was univariate and bivariate tests using the chi-square test. The data was collected by using questionnaire. Result: The results showed 20 people (56,3%) respondents were female, 12 people (43,8%) respondents were firstborn children, 20 (62,5%) respondents had never had previous treatment experience, 19 people(59,4%) chose caring behavior for less nurses and 18 people (56,3%) respondents experienced moderate anxiety. Based on statistical tests there was a correlation between sex with anxiety level p-value was 0,003, there was correlation between experience being treated in hospital with an anxiety level p-value was 0,001, there was a correlation between nurse caring behavior with an anxiety level p-value was 0,000. Discussion: There was a correlation among gender, experience in hospital care. Caring behavior of nurses with anxiety level of children experiencing hospitalization at the MuhammadiyahHospital Palembang in 2019.